Performance of Light Emitting Diode on Surface Machined Heat Sink - S. Shanmugan; D. Mutharasu; O. Zeng Yin (Institute of Advanced Engineering and Science, 2012)
In the point of efficient heat removal from light emitting diode (LED) package to ambient, the surface of the heat sinks must be finished based on required condition. The surface finishing plays an important role in efficient heat dissipation. In our work, the top surface of heat sink was machined like two different shapes (slotted and ‘W’ shaped) and tested the thermal performance for 3W green LED. The total thermal resistance was high for ‘W’ shaped surface at 100 mA. Surface modification was not influenced much on the thermal resistance (Rth) value at higher operating current. Noticeable increase on junction temperature was observed for ‘W’ shaped surface at 100 mA than slotted surface. In optical properties, low lux values were recorded for ‘W’ shaped surface at all operating current. In addition, ‘W’ shaped surface showed low value in CRI than other two surfaces (plain and slotted). The observed CCT value was decreased as the measuring time increased. High value in CCT was observed for ‘W’ shaped surface at higher operating current (> 350mA). Slotted surface showed good performance on both thermal and optical properties of the given 3W green LED.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.2125